The Correlation Between the Revenues and the Social Media Profiles of French Companies on the Luxury Goods Market - Aftowicz, Agata (Biznesmaniak, 2020)
This article offers an analysis of the dependency between several French companies’ growth of popularity on social media and their revenues on the luxury goods market. Over the past five years, French companies have had the largest share in revenues in terms of luxury goods sold around the world. The article investigates the phenomenon in question by means of the monographic and the statistical methods.